The Evolution of Cholesterol-Rich Membrane in Oxygen Adaption: The Respiratory System as a Model - Zuniga-Hertz, Juan Pablo; Patel, Hemal H. (Frontiers in Physiology, 2019)
The increase in atmosphere oxygen levels imposed an important environmental pressure to the primitive organisms in regard with intracellular oxygen concentration management. Evidence suggest the raise of cholesterol, key molecule for cellular membrane organization, as a cellular strategy to restrain free oxygen diffusion under the new environmental conditions. During evolution and the increase in organisms complexity, cholesterol played a pivotal role in the establishment of novel and more complex functions associated with lipid membranes. Of these, cholesterol-rich membrane domains like caveolae have been suggested as an important in situ functional hub with extended regulatory functions. Oxygen diffusion and transport in complex organisms was facilitated with the evolution of complex respiratory systems and molecular response mechanisms that ensure response to critical events such as hypoxia. Caveolae has been structural and functionally associated with respiratory systems and associated with oxygen diffusion control through its relation with molecular response systems like hypoxia inducible factors, HIFs, and particularly as an in membrane oxygen sensor, controlling oxygen diffusion according with cellular physiological requirements.